The Interaction of Islam and Culture and The Values of Islamic Education In The ‘Mangonggo’ Tradition In Batetangnga Village - Suddin Bani; Burhanuddin; Aan Setiawan (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
This article examines the tradition of Mangonggo within the Pattae tribal community, highlighting the interaction between local culture and Islamic teachings in Batetangnga. The Mangonggo durian is a traditional activity conducted by the Batetangnga community during periods of abundant fruit harvest. According to community leaders, this tradition predates the administrative establishment of Batetangnga village. The tradition embodies significant Islamic educational values. However, contemporary influences, including pragmatism and differing religious perspectives, have raised concerns about the preservation of this tradition. This research employs a qualitative methodology, with the researcher serving as the primary instrument for data collection through observation and interviews. The aim is to understand the challenges associated with preserving the Mangonggo tradition. In qualitative research, subjects are selected purposively; thus, this study will utilize purposive sampling to ensure that the data collected aligns with the research objectives. The findings of this study indicate that the Mangonggo durian tradition is a product of the interplay between culture and Islam within the Batetangnga community. This interaction is evident in the incorporation of religious symbols and instruments in the implementation process such as using the mosque as an information center, conducting prayers with religious texts, shifting societal paradigms, and involving religious leaders. Furthermore, the Mangonggo tradition, as a manifestation of the convergence of religion and culture, encompasses numerous Islamic educational values, including gratitude, sincerity, honesty, humility, and collaborative cooperation. The preservation of this local culture, exemplified by the Mangonggo tradition, serves as an alternative means of promoting Islam within the Batetangnga Village community. This approach has garnered government support as part of the religious moderation program, which emphasizes the importance of accommodating local culture.